MEMBANGUN KEMBALI KESETARAAN GENDER DENGAN ADAT BERSENDI SYARA’: PRAKTIK, IMPLIKASI DAN TANTANGANNYA - Momy A Hunowu; Hatim Badu Pakuna; Amir Fadhilah; Pardamean Daulay (Farabi, 2026)
From the 15th to the 17th century, Gorontalo women alternated with men in holding royal power for many years. This gender equality, which lasted for three centuries, began to erode with the arrival of colonial powers. Fears of sexual violence led parents to hide their daughters, causing prolonged psychological pressure and eventual marginalization. After independence, adat bersendi syara’ rituals sought to restore balance by honoring women and creating space for their resurgence. This study aims to explore traditional practices that uplift women, their implications for gender equality, and the challenges of preserving these values. Findings show that rituals for women begin early in life to instill purity, dignity, and confidence so they may grow into pious individuals. These rituals protect women from violence, internalize Islamic teachings, and strengthen their self-confidence. However, over the past century, patriarchy, the profanization of rituals, the expansion of formal education, and globalization have hindered the optimization of women’s roles. These findings are crucial for strengthening gender equality grounded in Islam and local cultural traditions.